JOB PERFORMANCE AND EMPLOYEE MOTIVATION AMONG NON-ACADEMIC STAFF AT A PUBLIC UNIVERSITY IN SARAWAK, MALAYSIA - Norlina Mohamed Noor; Puteri Faida Alya Zainuddin; Abang Fhaeizdhyall Abang Madaud; Imelda Nara (Jurnal Penyelidikan Sains Sosial, 2020)
Today, most employers would like to have their employee feels ready to work and be motivated but still do not understand what truly motivates a person. This paper is to measure the effect of employee motivation on job performance among non-academic staff in a public university in Sarawak, Malaysia. A total of 97 respondents were selected from the non-academic staff in the public university. In this study, the quantitative data collection started with the design of a set of questionnaires and followed by content validity checks. The independent variables for this study are working environment, individual needs, and personal preferences. The analysis shows all three variables are positively and significantly related to job performance. This study would give benefits to employees because it would provide enough information that would help the employees to understand that motivation can affect their job performance. Besides that, it can help the organization to increase their productivity as motivation was an essential element in producing job performance. Lastly, this study would provide future researchers as a reference to uncover intervention studies related to motivation.